Gender Issues in an Ageing Society - Austen, Siobhan (Wiley-Blackwell Publishing Asia, 2016)
Many aspects of our ageing society are deeply gendered. The number of older women is substantially larger than the number of older men. Women are also more likely than men to live the latter part of their life without a spouse. Relatedly, they are more likely than men to be involved in caring for other ill or disabled older family members. This article examines how the combination of gender differences in life expectancy, marriage, care roles, workforce participation and current policy settings combine to produce gender inequality in old age. It identifies policy measures to redress this imbalance.